2007
DOI: 10.1074/jbc.m704357200
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Phosphoinositide 3-Kinase C2α in Insulin Signaling

Abstract: The members of the class II phosphoinositide 3-kinase (PI3K) family can be activated by several stimuli, indicating that these enzymes can regulate many intracellular processes. Nevertheless, to date, there has been no definitive identification of their in vivo product, their mechanism(s) of activation, or their precise intracellular roles. By metabolic labeling, we here identify phosphatidylinositol 3-phosphate as the sole in vivo product of the insulin-dependent activation of PI3K-C2␣, confirming the emergin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
160
4
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(170 citation statements)
references
References 71 publications
5
160
4
1
Order By: Relevance
“…Consistent with this, C2α was detected in a granular pattern in HUVEC with enrichment in the perinuclear region, and partially co-localized with markers of clathrin-coated vesicles, TGN and early endosomes ( Supplementary Fig. 14a-c) 16,18,22 . GFP-C2α also substantially overlapped with mRFP-2×FYVE ( Supplementary Fig.…”
supporting
confidence: 58%
See 3 more Smart Citations
“…Consistent with this, C2α was detected in a granular pattern in HUVEC with enrichment in the perinuclear region, and partially co-localized with markers of clathrin-coated vesicles, TGN and early endosomes ( Supplementary Fig. 14a-c) 16,18,22 . GFP-C2α also substantially overlapped with mRFP-2×FYVE ( Supplementary Fig.…”
supporting
confidence: 58%
“…The actions of C2α and class I PI3Ks in EC are distinct in that, different from C2α, class I PI3Ks exert a great impact on Akt stimulation and cell proliferation and are not involved in vesicular trafficking including VE-cadherin transfer or VE-cadherin assembly at the cell-cell junction [10][11][12][13] . Therefore, these observations reveal novel biological activities of C2α and underscore broader roles for PI3K family members in vascular physiology and pathophysiology.In contrast to class I PI3Ks that generate PtdIns(3,4,5)P 3 , the major product of class II and III PI3Ks is PtdIns(3)P, which is mainly accumulated in endosomes [16][17][18][20][21][22][23][24][25] .Consistent with this, C2α in EC was localized in endosomes and TGN, which are organelles responsible for processing, sorting and packaging proteins into distinct carriers for transport to their final destinations. Another class II PI3K-C2β and class III Vps34 are also localized primarily in the clathrin-coated or endocytic compartment 38,39 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In animal cells, PtdIns(3)P also localizes to early endosomes, where it is required for protein trafficking. More recently, it has been reported that PtdIns(3)P associates with the plasma cell membrane during responses to insulin (123) and that plasma membrane-associated PtdIns(3)P is required for both glucose transporter 4 protein translocation to the plasma membrane (123) and neurosecretory granule release (124). PtdIns(3)P is generally found on the cytoplasmic leaflet of internal membranes.…”
Section: Discussionmentioning
confidence: 99%